Re-vamped! - Mercer, Sienna (New York : HarperTrophy, 2007)
When Olivia and Ivy tell their classmates and parents that they are identical twins, the word spreads to the vampire officials and Olivia must prove that she is worthy of keeping Ivy's true identity a secret.
750
Accelerated Reader AR
Keywords: Vampires -- Juvenile fiction; Twins -- Juvenile fiction; Sisters -- Juvenile fiction; Prejudices -- Juvenile fiction; Schools -- Juvenile fiction